Wavelet scalogram analysis of phonopulmonographic signals. (1st January 2013) - Gautam, N.K.; Pokle, Sanjay B.
Mortality rate due to lung-related diseases can be minimised by a precise preliminary diagnosis technique. Human lung sound (respiratory sound) has the diagnostic potential that helps the physician to diagnose the pulmonary disease and some other disorders of their patient. Lung auscultation in phonopulmonographic configuration will become more reliable and accurate diagnostic tool by effective lung sound signal analysis. In this paper a time frequency analysis of normal and abnormal acquired lung sound signals is presented to differentiate between normal and abnormal case. For this purpose, wavelet transform-based scalogram is drawn and analysed. The result of this analysis showed that it has a potential to effectively differentiate between normal and abnormal cases.